Case Report: ICIs-induced Guillain–Barré syndrome recovered from mycophenolate mofetil - Ding, Mengge; Deng, Chao; Liu, Xianling; Jiang, Shun; Gao, Yuan; Fan, Dan; Zhou, Yiguang; He, Jiangbo; Liu, Chaoyuan (Frontiers in Immunology, 2023)
The emergence of immune checkpoint inhibitors (ICIs) has significantly prolonged the survival time of cancer patients. However, it may also lead to various immune-related adverse events (irAEs), including Guillain–Barré syndrome (GBS), a rare type of irAE. Most GBS patients can recover spontaneously due to the self-limited nature of the disease, but severe cases can result in respiratory failure or even death. Here we report a rare case of GBS occurring in a 58-year-old male patient with non-small cell lung cancer (NSCLC) who developed muscle weakness and numbness of the extremities during chemotherapy combined with KN046, a PD-L1/CTLA-4 bispecific antibody. Despite receiving methylprednisolone and γ-globulin, the patient’s symptoms did not improve. However, there was significant improvement after treatment with mycophenolate mofetil (MM) capsules, which is not a routine regimen for GBS. To the best of our knowledge, this is the first reported case of ICIs-induced GBS that responded well to mycophenolate mofetil instead of methylprednisolone or γ-globulin. Thus, it provides a new treatment option for patients with ICIs-induced GBS.